2018
DOI: 10.1142/s0192415x18500271
|View full text |Cite
|
Sign up to set email alerts
|

Platycodin D Reverses Pathological Cardiac Hypertrophy and Fibrosis in Spontaneously Hypertensive Rats

Abstract: Platycodin D (PD) is the main active saponin isolated from Platycodon grandiflorum (PG) and is reported to exhibit anticancer, anti-angiogenic, anti-inflammation and anti-obesity biological effects. The current study aims to evaluate the therapeutic efficacy of PD in cardiac fibrosis and for hypertrophy in spontaneous hypertension rats (SHRs) and to verify inhibition of the signaling pathway. Significant increases in the cardiac functional indices of left ventricular internal diameter end diastole (LVIDd) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…DC., of the Campanulaceae family, which has traditionally been used to treat a variety of diseases in Korea, China, and Japan (Zhang et al 2015;Ji et al 2020). Recently, platycodin D has been shown to have multiple pharmacological properties, including anti-inflammatory (Fu et al 2018b;Ye et al 2019), immunostimulatory (Xie et al 2008), anti-cancer (Seo et al 2018;Huang et al 2019), antioxidant (Cho et al 2018;Wang et al 2018;Shi et al 2020), and inhibitory effects against various cardiovascular and metabolic diseases (Lin et al 2018;Liu et al 2020). The antioxidant activity of platycodin D has been primarily attributed to increased ROS scavenging activity and involves the activation of oxidative stress defense systems.…”
Section: Introductionmentioning
confidence: 99%
“…DC., of the Campanulaceae family, which has traditionally been used to treat a variety of diseases in Korea, China, and Japan (Zhang et al 2015;Ji et al 2020). Recently, platycodin D has been shown to have multiple pharmacological properties, including anti-inflammatory (Fu et al 2018b;Ye et al 2019), immunostimulatory (Xie et al 2008), anti-cancer (Seo et al 2018;Huang et al 2019), antioxidant (Cho et al 2018;Wang et al 2018;Shi et al 2020), and inhibitory effects against various cardiovascular and metabolic diseases (Lin et al 2018;Liu et al 2020). The antioxidant activity of platycodin D has been primarily attributed to increased ROS scavenging activity and involves the activation of oxidative stress defense systems.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from Molkentin et al, have explicitly demonstrated that pharmacological inhibition of this hypertrophic signaling pathway plays important for suppression of cardiac hypertrophy and heart failure . Additionally, recent report from our group has highlighted the attenuation of these signaling mediators for suppression of Ang‐II induced cardiac hypertrophy …”
Section: Discussionmentioning
confidence: 81%
“…Investigation of methods of interfering with fi broblast activation may thus provide novel therapeutic strategies for the treatment of pulmonary fi brosis. Reports have demonstrated previously that PD reverses pathological myocardial hypertrophy and fi brosis in spontaneous hypertension rats (16). Additionally, PD improves liver fi brosis and activates hepatic stellate cells by regulating JNK/c-JUN signal pathway (17).…”
Section: Discussionmentioning
confidence: 95%
“…To date, PD has received extensive attention due to its reported anti-infl ammatory, antiviral, antifi brosis and anti-cancer roles (12)(13)(14)(15). It has been well reported that PD reverses pathological myocardial hypertrophy and fi brosis in spontaneous hypertension rats (16). A study mentioned that by regulating JNK/c-JUN signal pathway, PD improves liver fi brosis and activates hepatic stellate cells (17).…”
Section: Introductionmentioning
confidence: 99%